Reduced Expression of Membrane Complement Regulatory Protein CD59 on Leukocytes following Lung Transplantation - Michielsen, Laura A.; Budding, Kevin; Drop, Daniël; van de Graaf, Ed A.; Kardol-Hoefnagel, Tineke; Verhaar, Marianne C.; van Zuilen, Arjan D.; Otten, Henny G. (Frontiers in Immunology, 2018)
Cellular protection against undesired effects of complement activation is provided by expression of membrane-bound complement regulatory proteins including CD59. This protein prevents membrane attack complex formation and is considered to be involved in graft accommodation. Also, CD59 downregulates CD4+ and CD8+ T cell activation and proliferation. It is unknown whether CD59 expression is affected by transplantation. The aim of this study was to evaluate the quantitative CD59 antigen expression on distinct leukocyte subsets following lung transplantation (n=26) and to investigate whether this differs from pretransplantation (n=9). The results show that CD59 expression on leukocytes is significantly lower posttransplantation compared to healthy controls (p=0.002) and pretransplantation (p<0.0001). Moreover, the CD59 expression diminishes posttransplantation on all distinct lymphocyte subsets (p<0.02). This effect appeared to be specific for CD59 since the expression of other surface markers remained stable or inclined following transplantation. The highest antigen expression posttransplantation was observed on CD4+ T cells and monocytes (p≤0.002). These findings show that CD59 expression on leukocytes diminishes posttransplantation which could result in decreased resistance against complement and enhanced T cell activation. If such reduction in CD59 expression also occurs on endothelial cells from the transplanted organ this could lead to a change into a prothrombotic and proinflammatory phenotype.